2018
DOI: 10.1155/2018/4714836
|View full text |Cite
|
Sign up to set email alerts
|

Association of NLRP1 and NLRP3 Polymorphisms with Psoriasis Vulgaris Risk in the Chinese Han Population

Abstract: Aim To clarify the association between the single nucleotide polymorphisms (SNPs) in the NLRP1 and NLRP3 and Psoriasis Vulgaris (PsV) in the Chinese Han population. Methods We genotyped eight SNPs, four from NLRP1 (rs8079034, rs11651270, rs11657747, and rs878329) and NLRP3 (rs7512998, rs3806265, rs10754557, and rs10733113) each in 540 patients with PsV and 612 healthy controls in the Chinese Han population using an improved multiplexed ligation detection reaction (iMLDR) method. The genotype and haplotype freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…A study containing 1086 T1D cases and 3273 controls in Norway has demonstrated a significant association between the NLRP1 gene and T1D [13], while another two studies conducted in Poland and Northeast Brazil did not find such association [14, 15]. Our results showed that rs11651270 was significantly associated with T1D while another study confirmed that it was not related to psoriasis vulgaris [33]. Although we did not find a significant association between rs2670660 and T1D, this SNP has been reported to associate with many other autoimmune disorders, such as generalized vitiligo [18], systemic sclerosis [34], and systemic lupus erythematosus [35].…”
Section: Discussionsupporting
confidence: 52%
“…A study containing 1086 T1D cases and 3273 controls in Norway has demonstrated a significant association between the NLRP1 gene and T1D [13], while another two studies conducted in Poland and Northeast Brazil did not find such association [14, 15]. Our results showed that rs11651270 was significantly associated with T1D while another study confirmed that it was not related to psoriasis vulgaris [33]. Although we did not find a significant association between rs2670660 and T1D, this SNP has been reported to associate with many other autoimmune disorders, such as generalized vitiligo [18], systemic sclerosis [34], and systemic lupus erythematosus [35].…”
Section: Discussionsupporting
confidence: 52%
“…The activated NLRP3 inflammasome could result in the activation of ASC, caspase-1, and the release of mature IL-1β, and eventually promoted the development of inflammation [13]. Accordingly, the pathogenesis and progress of psoriasis were closely related to TLR7/8-MyD88-NF-κB and NLRP3 pathways [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…e etiopathogenesis of PsV is multigenic and multifactorial. Like our previous studies, [27] our study had several limitations. First, our sample size was relatively small, which may limit the revelation of true relationships.…”
Section: Discussionmentioning
confidence: 85%
“…CARD8 may be involved in psoriasis development as a genetic marker or a causative polymorphism. Previously, our team identified a relationship between several other genetic polymorphisms and PsV [14,[27][28][29]. We will compile these findings to further explore the relationship between these genes and PsV in the Han population of northeastern China.…”
Section: Resultsmentioning
confidence: 93%